2017
DOI: 10.1101/195198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-128 inhibits telomerase activity by targeting TERT mRNA

Abstract: NOVELTY AND IMPACTTelomerase is an RNA-dependent DNA polymerase that synthesizes telomeric DNA sequences and almost universally provides the molecular basis for unlimited proliferative potential.Expression of human telomerase alone is sufficient for the immortalization of diverse cell types.We have identified the tumor suppressor microRNA (miR-128) as a novel regulator of telomerase, which directly targets the coding sequence (CDS) of TERT mRNA and significantly represses Tert protein expression in a panel of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Likewise, miR-1182, miR-1266, miR-532, miR-1207-5p, and miR-3064 suppress gastric, bladder, ovarian cancer growth and invasion by binding to the TERT 3’UTR ( 10 , 79 , 84 , 85 ). Furthermore, miR-128 was found to control TERT expression in HeLa and teratoma cell lines ( 81 , 86 ).…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Likewise, miR-1182, miR-1266, miR-532, miR-1207-5p, and miR-3064 suppress gastric, bladder, ovarian cancer growth and invasion by binding to the TERT 3’UTR ( 10 , 79 , 84 , 85 ). Furthermore, miR-128 was found to control TERT expression in HeLa and teratoma cell lines ( 81 , 86 ).…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Carcinogenic miRNAs may exist as oncogenic miRNAs or suppressor miRNAs that promote or inhibit the development of cancer, respectively. Several miRNAs (miR-128, miR-138, miR-1182, miR-342, miR-491, and miR-541) negatively regulate the expression of the TERT gene, thereby acting as tumor suppressor miRNAs (109). Overexpression of miR-138 has been shown to inhibit cell proliferation, invasion and induce apoptosis in cervical cancer (110).…”
Section: Telomeres As a Possible Therapeutic Targetmentioning
confidence: 99%
“…Another study found that miR-1182 reduced the proliferation and migration of gastric cancer cells (112). In contrast, miR-128 can act as either oncogenic or suppressor miRNA, depending on interaction with various targets (109). TERC-targeted miRNAs may act as telomerase inhibitors and are being tested in clinical applications.…”
Section: Telomeres As a Possible Therapeutic Targetmentioning
confidence: 99%
“…miRNAs are a class of endogenous, noncoding RNAs with regulatory functions that are about 20 to 25 nucleotides in length and play different roles in tumorigenesis: oncogenic miRNAs promote cancer development and tumor suppressor miRNAs . MiRNAs regulate posttranscriptional expressions by complexing with RNA‐induced silencing complexes (RISCs) and base pairing with target mRNAs.…”
Section: Oligonucleotides Targeting Telomeres and Telomerasementioning
confidence: 99%